ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA PT. INCIPNA INDONESIA AMBON - Shella Kriekhoff (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The goal is to determine empirically the financial performance at PT Incipna Indonesia Ambon is already showing good financial condition by using the cash flow statement. The method of analysis used in this research is the analysis of the ratio of cash flow. Results of the analysis of the discussion in 2011 Ratio of cash flow shows the financial condition is not good, because of the seven ratios are taken into account in assessing the financial performance only three ratios that meet the standards that funds flow coverage ratio, interest coverage ratio and the ratio of cash for capital expenditures. While four other ratios less than one. But for the ratio of net free cash flow generated despite ratio less than one is considered good, because in addition be used to pay liabilities, the company's cash flow can also be used to make investments. In 2012 and 2013 is quite good because four of the seven ratios used meets the standards or are on top of which the funds flow coverage ratio, the ratio of cash to interest coverage ratio of capital expenditures, and the ratio of net free cash flow. Especially for the ratio of net free cash flow generated even though the ratio is more than one, but rated poorly because of the percentage ratios generated more than 100%, which means that all cash flows that are owned by the company only used to pay duty and could not make an investment.